Analysis of Student Political Behavior in Serang City - Zakaria Habib Al-Ra'zie; Maulana, Muhammad Akbar (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
Students are often considered as agents of change who have great hopes to improve the conditions of society. Through political involvement, students can provide input and demands to the government so that the policies produced are for the benefit of the wider community. However, the implementation of this political action is greatly influenced by students' perceptions of basic concepts and existing political realities, which further shape their political attitudes or behaviors. This research offers a novelty that focuses on the political behavior of students through their perception and participation in ongoing political dynamics. This research was conducted on students from various universities in Serang City, Banten Province, using qualitative methods. Data collection was carried out through literature studies and interviews, with descriptive and analytical data analysis. The results of the study show that political participation among students in Serang City is influenced by the resources and access to knowledge they have, both in the campus environment and in the academic network. In addition, students also have time to study, discuss, and advocate for policies that are perceived to be detrimental to society. However, even though they have this awareness and opportunity, students in Serang City tend not to show the desire to be actively involved in influencing political decisions, the public policy-making process, and leadership succession. This can be seen from their participation in the general election which is still procedural and has not reached a substantial level.